DINAMIKA RELIGIUSITAS SISWA MUSLIM DI SEKOLAH NON ISLAM (Studi Kasus Siswa Muslim SMA Santo Thomas Yogyakarta) - Rizky Setiawati; Nurhamidi Nurhamidi (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2014)
The purpose of this study was to determine the dynamics of religiosity muslim students in high school St. Thomas Yogyakarta associated with environmental and pluralist religious education. This study is a qualitative research that takes place at St. Thomas High School in Yogyakarta. The approach used is the anthropological approach to religion, is used to examine the dynamics of deep religiosity of Muslim students in accordance with what is understood and experienced by research subjects concerned.Data was collected through observation, interviews, documentation, and triangulation. The data obtained and analyzed by descriptive-analytical, meaning that the results of the analysis in the form of exposure picture of the situation observed in the form of a narrative description. The data were analyzed by using inductive pattern, namely: data reduction, data presentation and conclusion.The results showed that the dynamics of muslim religiosity in the high school students of St. Thomas views of the dimensions of religious belief, religious practices, religious feeling, religious knowledge, religious and community effect is still not good. Islamic religious education ever obtained or obtainable Education Religiosity is currently not so influential in their lives. Of course this is also due to the lack of motivation of the student as well as a lack of support from parties or organizations outside the school in improving the student’s religiosity.